Telomere-dependent and telomere-independent roles of RAP1 in regulating human stem cell homeostasis. Issue 9 (22nd February 2019) - Zhang, Xing; Liu, Zunpeng; Liu, Xiaoqian; Wang, Si; Zhang, Yiyuan; He, Xiaojuan; Sun, Shuhui; Ma, Shuai; Shyh-Chang, Ng; Liu, Feng; Wang, Qiang; Wang, Xiaoqun; et al.
Abstract: RAP1 is a well-known telomere-binding protein, but its functions in human stem cells have remained unclear. Here we generated RAP1-deficient human embryonic stem cells (hESCs) by using CRISPR/Cas9 technique and obtained RAP1-deficient human mesenchymal stem cells (hMSCs) and neural stem cells (hNSCs) via directed differentiation. In both hMSCs and hNSCs, RAP1 not only negatively regulated telomere length but also acted as a transcriptional regulator of RELN by tuning the methylation status of its gene promoter. RAP1 deficiency enhanced self-renewal and delayed senescence in hMSCs, but not in hNSCs, suggesting complicated lineage-specific effects of RAP1 in adult stem cells. Altogether, these results demonstrate for the first time that RAP1 plays both telomeric and nontelomeric roles in regulating human stem cell homeostasis.